Determination of Organochlorine Pesticide Residues in Tobaccos by Capillary Gas Chromatography - Cai, Jibao; Gao, Yun; Zhu, Xiaolan; Shen, Zhonglan; Su, Qinge (Asian Journal of Chemistry, 2016)
A simple, rapid, relative reliable method for extraction of 17 organochlorine pesticides in tobaccos and their determination by capillary gas chromatography was presented. The pesticides were extracted and cleaned-up by a Soxhlet extractor with hexane as extracting solvent. Different methods were compared for the determination of organochlorine pesticides in tobaccos. The Soxhlet extraction was evaluated for organochlorine pesticides analyses in tobaccos while liquid-liquid partition and solid phase extraction methods were compared. Of all the extracting methods used, Soxhlet extraction gave the best results.